Ontology summarization technology survey - Yuehang DING; Hongtao YU; Ruiyang HUANG; Yingle LI (网络与信息安全学报)
Ontology is an important tool for knowledge sharing,while it is also the upper structure of knowledge graph.With the explosion of data and ontology complexity,ontology understanding and application are becoming more and more difficult.As a technique to shrink ontology scale,ontology summarization accelerated ontology understanding and application technologically.Different definitions of ontology summarization were shown,ontology summarization methods were compared and analyzed,ontology summarization evaluation parameter system was introduced,and at last,possible future research area was given.